Determinants of Motor Vehicle Tax Compliance In Surakarta City - Afifah Hasna Sayyidah; Astuning Saharsini (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
The aim of this study was to ascertain the effects of tax penalties, service standards, socialization, and tax awareness on motor vehicle taxpayer compliance in the city of Surakarta. The data source that is used is primary data. The study population consisted of 244,195 individuals. Because accidental sampling was the method used, 100 people made up the sample. Multiple regression analysis, hypothesis testing, data instrument testing, and classical assumption testing are the data analysis techniques that are employed. Based on research findings, tax socialization, tax awareness, service quality, and tax sanctions all have an impact on partial compliance with mandatory motorized driving.